Abonamiento foliar orgánico en la producción de Biomasa y rendimiento del cultivo de Maíz Suave (Zea Mays l) raza pidicinco- Banda de Shilcayo-San Martín - Romero Vela, Dayani Shirley (2009)
Global warming is an alarming phenomenon, with disastrous consequences, which causes high concentrations of gases "greenhouse" (especially carbon dioxide, CO2), resulting primarily from human activity are. With the signing of the Kyoto Protocol in 1997, staying established the Framework Convention on Climate Change UN (UNFCCC). The objective of the Kyoto Protocol is to reduce emissions of global greenhouse gases on 1990 levels for the period 2008-2012 by 5.2%. This contains legally binding targets for industrialized countries to reduce emissions of six greenhouse gases of human origin such as carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O), plus three fluorinated industrial gases: hydrofluorocarbons (HFCs), perfluorocarbons (PFCs) and sulfur hexafluoride. Thus began in all signatory countries a new stream of research aimed at estimating carbon sequestration by different crop or plants in different ecosystems, with the possibility of establishing an emissions trading between industrialized countries use of ecosystems as carbon stores assigning values ​​that would be payments from industrialized countries, etc. In Peru, the corn crop is used in production of different ecosystems coastal mountains and jungle, both varieties of yellow corn and starchy. In the Selva region grows some of the races of maize, Pidicinco, traditionally low yields of 0.5 to 1.0 t / ha (Oral information from farmers, 2008), with exclusive use for direct consumption as corn creams, corn beer, flour, tamales, tamales, etc; References on many unknown parameters and performance even on the biomass and carbon sequestration generated. Thus, and as an alternative to improve the productivity of this breed grain corn using leaf compost (Biol), the production of biomass and crop yield soft corn (Zea mays L.) was estimated Raza Pidicinco in District Band Shilcayo - San Martín ".